Public opinion and awareness regarding probation in the Czech Republic - Tomášek, Jan (European journal of probation, 2022)
Previous research on non-custodial sentences has pointed to the association between awareness of alternatives to prison and public opinion on these alternative measures. Using data from a public opinion survey conducted in the Czech Republic in 2018, the main objective of this study is to examine the extent to which public opinion on probation is influenced by awareness of probation service and support for probation in general. The data suggest that those generally in favour of probation, unlike those opposed, agree with this measure being imposed on a wider range of offenders, are more lenient towards offenders who violate the conditions of their probation, and perceive probation as being beneficial to the criminal justice system and society as a whole. On the other hand, the public’s awareness of the probation service per se seems not to be as important as whether or not the basic principles of probation are embraced.